New species for Thraulodes Ulmer, 1920 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) and the first key to adults from Brazil - Lima, Lucas R.c.; Mariano, Rodolfo; Pinheiro, Ulisses (Zootaxa, 2013)
Four new species of the mayfly genus Thraulodes Ulmer are described based on imagos from Northeastern and Southern Brazil: Thraulodes luizgonzagai sp. nov., Thraulodes sternimaculatus sp. nov., Thraulodes alapictus sp. nov., and Thraulodes pinhoi sp. nov. The new species can be easily differentiated by the abdominal color pattern and genitalia morphology. The first key to adults from Brazil is provided.